Stell & Maran’s Text Book of Head and Neck Surgery and Oncology: Fifth Edition - Baskota, Dharma Kanta (Nepalese Journal of ENT Head and Neck Surgery, 2014)
DOI: http://dx.doi.org/10.3126/njenthns.v3i2.10164 Nepalese Journal of Head and Neck Surgery Vol.3(2) 2012: 31